THE FORMS OF REQUESTING IMPERATIVE SENTENCES IN 'DJARUM 76' CIGARETTE ADVERTISEMENTS (BENTUK-BENTUK KALIMAT IMPERATIF PERMINTAAN PADA IKLAN ROKOK 'DJARUM 76') - Hodairiyah Hodairiyah; Faris Febri Utama (UIN Raden Mas Said Surakarta, 2019)
This study focused on the structures of requesting imperative sentences of Djarum 76 cigarette advertisement. The researchers tried to explain the types, structures, and markers on verbal requests which appear on Djarum 76 advertisements on TV during 2009-2014. This study applied descriptive qualitative method. The data were requesting sentences in the advertisements of Djarum 76 which wre taken from Youtube website. The process of data collection involved watching, listening, and note taking technique. Meanwhile, for data analysis, the researchers applied distributional method. The results of this study show that: (1) not all requesting sentences on Djarum 76 advertisements omitted their subjects which referred to the speakers; (2) the requests could be expressed in different ways, such as by using a minor sentence and not a clause which refer to theÂ previous sentence as well as using nominal phrase (e.g.kuda poni)Â as what appeared on six advertisements. In addition, requesting sentences on advertisement of Djarum 76 had some different markers for requesting sentences compared to what is stated in the existing theories, such in the use of the words mau, pengin, dan jadikan contrasted to the common term minta.